The Arctic Traits Database – a repository of Arctic benthic invertebrate traits - Renate Degen (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Sarah Faulwetter (Department of Zoology, University of Patras) (Earth System Science Data, 2019)
The abstract is available here: https://uscholar.univie.ac.at/o:1142559 The abstract is available here: https://uscholar.univie.ac.at/o:1142559